2009
DOI: 10.1097/nnr.0b013e318199b52a
|View full text |Cite
|
Sign up to set email alerts
|

Factors Identified by Experts to Support Decision Making for Post Acute Referral

Abstract: Background-Each year, more than 13 million post acute referral decisions are made for Medicare recipients, yet there are no national, empirically derived decision support tools to assist in making these important decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…Our study partially confirmed the factors reported by Bowles et al [7] to identify the patients' requiring post-discharge care. In particular, they were important to determine their level of healthcare dependency: the presence of at least two neurological diseases and the lack of autonomy in carrying out IADLs (e.g., using public transport, preparing their meals, using money, taking medication, getting washed and dressed, and telephoning).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our study partially confirmed the factors reported by Bowles et al [7] to identify the patients' requiring post-discharge care. In particular, they were important to determine their level of healthcare dependency: the presence of at least two neurological diseases and the lack of autonomy in carrying out IADLs (e.g., using public transport, preparing their meals, using money, taking medication, getting washed and dressed, and telephoning).…”
Section: Discussionsupporting
confidence: 81%
“…On the basis of a review of retrospective, prospective, and mixed studies focusing on planning discharge for older hospitalized patients, Bowles et al [7] came to the conclusion that older people with intermittent or no domiciliary support, with difficulty walking, poor awareness of their own health conditions, long hospital stay, depression, and a large number of comorbidities should have the priority to be receive post-discharge services.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing readmissions thr-ough better discharge planning (DP) and transitional care is an international priority and many teams are working on solutions to improve this measure of quality (Bauer, Fitzgerald, Haesler, & Manfrin, 2009; Boling, 2009; BOOSTing Care Transitions Resource Room Project Team, 2008; Boutwell, Griffin, Hwu, & Shannon, 2009 March; Bowles et al, 2009; Coleman, Parry, Chahners, & Min, 2006; Graumlich et al, 2009; Jack et al, 2009; Naylor et al, 1999, 2004; Preyde, Macaulay, & Dingwall, 2009; Shepperd et al, 2010). A critical step of the process occurs when the clinical team decides whether or not to refer the patient for post-acute care (PAC) services such as skilled home care, inpatient rehabilitation, or skilled nursing facility care.…”
mentioning
confidence: 99%
“…This study tested the effect of an evidence-based screening tool, the Discharge Decision Support System (D2S2), that supports clinicians’ discharge referral decision making by identifying high-risk patients who need a referral for PAC (Bowles .et al, 2008, 2009). The study examined whether alerting hospital case managers about high-risk patients would result in better discharge plans as evidenced by time to first hospital readmission.…”
mentioning
confidence: 99%
“…2,3 Experts were able to identify 26 characteristics of patients (documented mainly by nurses) that are important to consider when making referral decisions. Through statistical modeling, a six-item risk-screening tool emerged, which provides advice to busy discharge planners about patients who are at risk for poor discharge outcomes and may benefit from postacute care.…”
Section: Data To the Rescuementioning
confidence: 99%